Meningkatkan Ketahanan Duduk Melalui Media Mozaik Bagi Anak Autis di SLB Autisma Yppa Padang - utami, syakinah putri (RC-INSTITUT, 2019)
One of the obstacles experienced by autistic children is the duration of sitting endurance of autistic children is low. This problem was found in SLB Autisma YPPA Padang. Where autistic children have a low duration of sitting resistance. The purpose of this study is to prove the mosaic media in increasing the sitting endurance of autistic children in SLB Autisma YPPA Padang. This study focused on measuring the duration of sitting endurance when given mosaic media. Researchers and children are involved in making mosaics. The type of research used is Single Subject Research with A-B-A design. A1 baseline condition consists of four meetings, the intervention condition consists of seven meetings and the second baseline condition consists of four meetings. Data collection methods in this study used event recording by calculating how long the duration of sitting endurance is based on direct observation. Data were analyzed using visual and graphical analysis. The results of the study stated that mosaic media can increase the duration of the child's sitting endurance during the learning process.